Flame-retardant composite PVC alloy material and preparation method thereof

By compounding PVC with acrylonitrile-styrene copolymer resin (AS) and zinc chloride (ZnCl2) to form a composite carbon layer, the problems of flame retardant migration and segregation and poor thermal stability of PVC materials are solved, achieving a highly efficient and uniform flame retardant effect, suitable for products such as refrigerator bottom panels, tea bar machine back panels, etc.

CN122255619APending Publication Date: 2026-06-23ANHUI HIGASKET PLASTICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610711900.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-22
Publication Date
2026-06-23

Smart Images

  • Figure CN122255619A_ABST
    Figure CN122255619A_ABST
Patent Text Reader

Abstract

The application provides a flame-retardant composite PVC alloy material and a preparation method thereof, and belongs to the technical field of flame-retardant materials.The flame-retardant composite PVC alloy material contains PVC, AS and ZnCl2 in components;in a combustion process, ZnCl2 can interact with the structure generated by the dehydrochlorination of PVC, the nitrile group of the acrylonitrile unit in AS and the aromatic structure of the styrene unit, promotes crosslinking of chain segments, cyclization of the nitrile group and aromatization reaction, and makes more combustible cracking products be converted into condensed phase residual carbon.At the same time, the existing technical prejudice that AS is flammable and flame retardant of PVC can only add flame retardant is overcome.Through the ingenious cooperation of the functions of the three components of PVC, AS and ZnCl2, the effect of jointly improving the flame-retardant property of the material is achieved.The flame-retardant composite PVC alloy material has good compatibility of components, uniform and excellent flame-retardant effect, no migration segregation, and no toxic gas generated in the combustion process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of flame retardant materials technology, aiming to improve the flame retardant performance of PVC materials. Specifically, it relates to a flame retardant composite PVC alloy material and its preparation method. Background Technology

[0002] PVC (polyvinyl chloride) is a polymer formed by the polymerization of vinyl chloride monomers under the action of initiators such as peroxides and azo compounds, or under the influence of light and heat, according to a free radical polymerization mechanism. Since its discovery, it has received widespread attention and, with the rapid development of the polymer industry, has been applied to all walks of life in human society.

[0003] PVC, as a general-purpose thermoplastic material, is characterized by low cost, wide availability, and stable chemical properties. It is an important component of engineering materials and is widely used in electronics, automotive parts, product packaging, and household goods, making it the second largest engineering plastic after polyethylene. Like other plastics, PVC has a certain degree of flammability, which greatly limits its application in some fields. To address the impact of PVC's flammability, current technology typically involves compounding flame retardants into PVC to improve its flame-retardant properties. This method is low-cost, more practical, and easier to industrialize.

[0004] Traditional flame retardants are mainly halogenated flame retardants, which mainly work by decomposing at high temperatures to release halogen free radicals to capture and transmit combustion free radicals, thereby stopping the free radical depolymerization process of the material to achieve a flame retardant effect. They can achieve high flame retardant efficiency with a small amount of additive. However, these flame retardants are prone to decomposition at high temperatures, producing a large amount of toxic gases, causing environmental pollutants, and posing a fire hazard in the event of a fire. They have been gradually replaced.

[0005] Phosphorus-nitrogen organic flame retardants decompose at high combustion temperatures to produce flame-retardant gases and leave a carbon layer as a residual flame retardant. Compared to halogen-based flame retardants, they exhibit good low toxicity. Existing PN-type flame retardants are widely used in various flame-retardant plastics. However, these flame retardants are prone to migration and segregation in high-temperature environments or during long-term service, resulting in uneven flame retardant effects. Furthermore, these flame retardants affect the thermal stability of polymers and produce a large amount of smoke during combustion.

[0006] In addition, inorganic flame retardants, such as aluminum hydroxide, magnesium hydroxide, and zinc borate, achieve their flame-retardant effect by releasing moisture and producing non-flammable inorganic oxides through high-temperature decomposition reactions. These flame retardants have extremely low toxicity and high flame-retardant efficiency. Furthermore, the expanded structure produced during decomposition has a certain heat insulation and smoke-suppressing effect, making them ideal flame-retardant materials. However, these inorganic materials have poor compatibility with the polymer matrix, significantly affecting the mechanical properties of the matrix. To address this issue, existing technologies modify the surface of inorganic flame retardants using compound coupling agents to uniformly disperse them within the matrix. However, practical studies have found that the condensation of the compounded coupling agent with the surface of the inorganic flame retardant affects its decomposition and expansion, resulting in a slow flame-retardant response and increased combustion smoke. Summary of the Invention

[0007] The purpose of this invention is to propose a flame-retardant composite PVC alloy material and its preparation method, so as to overcome the many technical problems existing in the common halogen-based flame retardants, phosphorus-nitrogen organic flame retardants and inorganic flame retardants in the prior art. The components of this flame-retardant composite PVC alloy material have good compatibility, uniform and excellent flame retardant effect, no migration segregation, and no toxic gas is generated during the combustion process.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0009] A flame-retardant composite PVC alloy material, comprising the following components in parts by weight:

[0010] Polyvinyl chloride (PVC): 100 parts;

[0011] Acrylonitrile-styrene copolymer resin (AS): 25~40 parts;

[0012] Zinc chloride (ZnCl2): 0.5~1.5 parts.

[0013] As a further preferred embodiment of the present invention, the flame-retardant composite PVC alloy material further includes the following components in parts by weight:

[0014] Dimethyl trimethoxymethylphosphonate: 1-10 parts.

[0015] As a further preferred embodiment of the present invention, the flame-retardant composite PVC alloy material further includes the following components in parts by weight:

[0016] Composite stabilizer: 1-3 parts;

[0017] Calcium carbonate: 5-10 parts;

[0018] Lubricant: 0.5~1.5 parts.

[0019] Preferably, in the flame-retardant composite PVC alloy material, the composite stabilizer includes hydrotalcite and calcium-zinc stabilizer. The lubricant includes PE wax and stearic acid.

[0020] When preparing flame-retardant composite PVC alloy material, the raw materials are mixed evenly by a high-speed mixer at a mixing temperature of 100~130℃, the extrusion temperature of the calendering process is 160~200℃, and the roller temperature is 150~200℃, thereby obtaining flame-retardant composite PVC alloy material.

[0021] The flame-retardant composite PVC alloy material proposed in this invention has the characteristics of good compatibility, no migration or segregation, and no toxic gas generation, and exhibits uniform and excellent flame-retardant effect. Compared with the prior art, the beneficial effects of this invention are detailed in the following aspects:

[0022] 1. This flame-retardant composite PVC alloy material contains PVC, AS and ZnCl2. During combustion, ZnCl2 can interact with the structure produced by PVC deHClation, the nitrile group of the acrylonitrile unit in AS and the aromatic structure of the styrene unit, promoting chain segment crosslinking, nitrile group cyclization and aromatization reactions, so that more combustible pyrolysis products are converted into condensed phase char.

[0023] 2. Both PVC and AS materials inherently possess a certain degree of flammability, which is common knowledge in this field. However, when PVC, AS, and ZnCl2 are compounded, a composite char layer is formed during combustion, enhancing the strength of PVC and achieving a 5VA flame retardant rating. This overcomes the existing technological bias that AS is flammable and PVC flame retardancy can only be achieved by adding flame retardants. Therefore, the compounding of PVC, AS, and ZnCl2 is not a superposition of the functions of individual components, but rather a clever combination of their functions to collectively improve the flame retardant performance of the material.

[0024] 3. Compared with traditional halogenated flame retardants, this invention solves the problem of toxic gas generation during the flame retardant process of PVC flame retardant materials, and does not release toxic gases during combustion. Compared with traditional phosphorus and nitrogen-based organic flame retardants, this invention solves the problems of poor thermal stability and uneven flame retardant effect caused by migration and segregation of PVC flame retardant materials. There is no migration and segregation problem in high-temperature environments or long-term service, thus the flame retardant effect is uniform. Compared with traditional inorganic flame retardants, this invention solves the problems of slow flame retardant reaction and increased combustion smoke caused by poor compatibility of PVC flame retardant materials. The polarity of AS in the proposed flame-retardant composite PVC alloy material matches that of PVC, the components have good compatibility, and the flame retardant effect is excellent. Attached Figure Description

[0025] Figure 1 These are actual images of the material prepared in Example 3 after combustion (a and b correspond to the front and back sides, respectively).

[0026] Figure 2 This is a comparison of the infrared spectra of the material prepared in Example 3 before and after combustion. Detailed Implementation

[0027] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings.

[0028] It should be noted that the raw materials used come from the following sources:

[0029] 1. Polyvinyl chloride (PVC): Tianjin Dagu Chemical Co., Ltd., DG-800 type.

[0030] 2. Acrylonitrile-styrene copolymer resin (AS): Chi Mei Industrial Co., Ltd., NF2200AR type.

[0031] 3. Zinc chloride (ZnCl2): Shanghai Maclean Biochemical Technology Co., Ltd.

[0032] 4. Composite stabilizer:

[0033] Hydrotalcite: Henan Wanshan New Material Technology Co., Ltd., uses hydrotalcite for PVC.

[0034] Calcium and zinc stabilizer: German brand Berloch, SW-251.

[0035] 5. Lubricant:

[0036] PE wax: Hangzhou Wangjiang Oil & Chemical Co., Ltd., CH-type.

[0037] Stearic acid: Indonesia Green Treasure Group, type 1801.

[0038] 6. Calcium carbonate: Jiangxi Bairui Calcium Carbonate Co., Ltd., 1250 mesh.

[0039] 7. Dimethyl trimethicone methylphosphonate: Anhui Zesheng Technology Co., Ltd., JX060674-5G.

[0040] Example 1:

[0041] The proportion of the flame-retardant composite PVC alloy material in this embodiment is as follows:

[0042] Polyvinyl chloride (PVC): 100 g.

[0043] Acrylonitrile-styrene copolymer resin (AS): 30 g.

[0044] Zinc chloride (ZnCl2): 1 g.

[0045] Dimethyl trimethoxymethylphosphonate: 3 g.

[0046] Hydrotalcite: 1.5 g.

[0047] Calcium carbonate: 6 g.

[0048] PE wax: 0.9 g.

[0049] The preparation method of the flame-retardant composite PVC alloy material in this embodiment is as follows:

[0050] The raw materials are mixed evenly using a high-speed mixer at a mixing temperature of 100°C. The extrusion temperature of the calendering process is 160°C, and the roller temperature is 150°C, to obtain a flame-retardant composite PVC alloy material.

[0051] Example 2:

[0052] The proportion of the flame-retardant composite PVC alloy material in this embodiment is as follows:

[0053] Polyvinyl chloride (PVC): 100 g.

[0054] Acrylonitrile-styrene copolymer resin (AS): 33 g.

[0055] Zinc chloride (ZnCl2): 1.1 g.

[0056] Dimethyl trimethoxymethylphosphonate: 4 g.

[0057] Hydrotalcite: 1.8 g.

[0058] Calcium carbonate: 7 g.

[0059] Stearic acid: 1 g.

[0060] The preparation method of the flame-retardant composite PVC alloy material in this embodiment is as follows:

[0061] The raw materials are mixed evenly using a high-speed mixer at a mixing temperature of 115°C. The extrusion temperature of the calendering process is 180°C, and the roller temperature is 175°C, to obtain a flame-retardant composite PVC alloy material.

[0062] Example 3:

[0063] The proportion of the flame-retardant composite PVC alloy material in this embodiment is as follows:

[0064] Polyvinyl chloride (PVC): 100 g.

[0065] Acrylonitrile-styrene copolymer resin (AS): 36 g.

[0066] Zinc chloride (ZnCl2): 1.2 g.

[0067] Dimethyl trimethoxymethylphosphonate: 5 g.

[0068] Calcium and zinc stabilizer: 2 g.

[0069] Calcium carbonate: 8 g.

[0070] Stearic acid: 1.2 g.

[0071] The preparation method of the flame-retardant composite PVC alloy material in this embodiment is as follows:

[0072] The raw materials are mixed evenly using a high-speed mixer at a mixing temperature of 130°C. The extrusion temperature of the calendering process is 200°C, and the roller temperature is 200°C, to obtain a flame-retardant composite PVC alloy material.

[0073] Comparative Example 1:

[0074] Compared to Example 1, zinc chloride was not added, but everything else was the same as in Example 1.

[0075] Comparative Example 2:

[0076] Compared with Example 1, AS is not added, and the rest is the same as Example 1.

[0077] Comparative Example 3:

[0078] Compared to Example 1, AS was replaced with polystyrene (PS), otherwise the same as in Example 1.

[0079] Combustion tests were conducted using a UL94 combustion tester, and smoke density was tested in accordance with GB / T 8323.2-2018 standard.

[0080] The PVC material prepared above is loaded into a flat vulcanizing machine, the temperature is controlled at 180±5℃, the pressure is 10MPa, and the holding pressure hot pressing time is 5min. The PVC material is pressed into a sheet blank. A sample is taken from the sheet blank and a tensile test is performed according to GB / T 1040.1-2025 standard. The tensile rate is 100mm / min, and a sample with a thickness of 2mm is prepared.

[0081] The ball pressure test (75℃) was conducted in accordance with the standard GB / T 5169.21-2017.

[0082] The 5VA test was conducted in accordance with the UL94 standard.

[0083] Table 1. Parameters and Results of Different Processes

[0084] Serial Number Tensile strength / MPa Does it meet the 5VA requirement? Smoke density (mg / g) Ball pressure / mm Example 1 31.3 satisfy 92 1.83 Example 2 35.5 satisfy 68 1.62 Example 3 38.2 satisfy 54 1.42 Comparative Example 1 31.1 Not satisfied 138 1.85 Comparative Example 2 21.6 Not satisfied 165 3.15 Comparative Example 3 29.8 Not satisfied 116 2.11

[0085] Comparative analysis of Examples 1, 2, 3 and Comparative Example 1 shows that, without zinc chloride, there is no promoting effect during combustion, and more condensed phase char residue is not formed. Therefore, the combustion rating does not meet 5VA, and the smoke density is 138 mg / g, which does not meet the smoke density standard. The ball pressure is similar to that of Example 1.

[0086] Comparative analysis of Examples 1, 2, 3 and Comparative Example 2 shows that, without AS, aromatic organic char and composite char layer cannot be formed. Therefore, the combustion rating does not meet 5VA, and the smoke density is 165 mg / g, which does not meet the smoke density standard. The ball pressure is 3.15 mm at 75°C because no AS was added, which is unqualified.

[0087] By comparing Examples 1, 2, 3 and Comparative Example 3, it can be seen that when PS is added to replace AS, although a composite carbon layer exists, the compatibility is poor and the carbon strength formed by combustion is insufficient, thus failing to meet the 5VA standard. The smoke density is 116 mg / g, which does not meet the smoke density standard. Furthermore, due to the insufficient compatibility between PVC and PS, its ball pressure also fails to meet the standard.

[0088] Figure 1 These are actual images of the burnt product from Example 3 (a and b correspond to the front and back sides, respectively). Figure 2 This is a comparison of the infrared spectra before and after combustion in Example 3. The infrared results show that the C-Cl related peaks in the sample changed after combustion, from 1600 to 1630 cm⁻¹. -1 Nearby conjugated / aromatic structural signals, 3370-3470 cm -1 The presence of nearby hydroxyl / adsorbed water signals and low wavenumber peaks related to zinc-containing inorganic residues indicates the formation of a composite char layer containing aromatic organic char and zinc-containing inorganic components on the combustion surface. This composite char layer can block the transfer of heat, oxygen, and combustible volatiles, thereby improving the flame retardant properties of the PVC composition. Simultaneously, the phosphorus element in dimethyl trimethylsilyl methylphosphonate promotes the formation of the char layer during PVC combustion, while the silicon element forms silicon dioxide, thereby enhancing the char layer strength and further synergistically enhancing the flame retardant effect. Therefore, this confirms that during the combustion of this flame-retardant composite PVC alloy material, ZnCl2 can interact with the structures produced by PVC deHClation, the nitrile groups of acrylonitrile units in AS, and the aromatic structures of styrene units, promoting segment crosslinking, nitrile cyclization, and aromatization reactions, resulting in more combustible pyrolysis products being converted into condensed-phase char residues.

[0089] In summary, this invention uses PVC, AS resin, and zinc chloride as the main components, achieving a 5VA level flame retardant effect. It solves the problems of uneven distribution, migration, and segregation of flame retardants caused by the addition of flame retardants in existing PVC flame retardant materials. The product has stable quality and excellent flame retardant effect. This flame-retardant composite PVC alloy material can be applied to multiple product fields such as refrigerator bottom panels, tea bar machine back panels, and compressor rear grilles.

Claims

1. A flame-retardant composite PVC alloy material, characterized in that, The components include the following parts by weight: Polyvinyl chloride (PVC): 100 parts; Acrylonitrile-styrene copolymer resin (AS): 25~40 parts; Zinc chloride (ZnCl2): 0.5~1.5 parts.

2. The flame-retardant composite PVC alloy material as described in claim 1, characterized in that, It also includes the following components in parts by weight: Dimethyl trimethoxymethylphosphonate: 1-10 parts.

3. The flame-retardant composite PVC alloy material as described in claim 2, characterized in that, It also includes the following components in parts by weight: Composite stabilizer: 1-3 parts; Calcium carbonate: 5-10 parts; Lubricant: 0.5~1.5 parts.

4. The flame-retardant composite PVC alloy material as described in claim 3, characterized in that, The composite stabilizer includes hydrotalcite and calcium-zinc stabilizer.

5. The flame-retardant composite PVC alloy material as described in claim 3, characterized in that, The lubricant includes PE wax and stearic acid.

6. A method for preparing the flame-retardant composite PVC alloy material as described in any one of claims 1 to 5, characterized in that, The raw materials are mixed evenly using a high-speed mixer at a mixing temperature of 100~130℃, and the extrusion temperature of the calendering process is 160~200℃, with a roller temperature of 150~200℃, thereby obtaining a flame-retardant composite PVC alloy material.